연령층별 성인의 개인구강관리보조용품 사용 여부와의 관련성 - 문정은; Jung Eun Moon; 이은주; Eun Ju Lee (Han'guk Ch'iwisaeng Hakhoe chi, 2016)
Objectives: This study aims to investigate the elements to affect the usage of individual oral hygiene devices in adults by the age group, to make the community inhabitants keep their healthy dental hygiene status, and to provide them with the educational materials for the dental hygiene and the basic data for the program development. The purpose of the study is to investigate the relation ot use of oral hygiene devices in the adults. Methods: The subjects were 9,073 adults from the sixth KNHANES from January, 2013 to December, 2014. The study consisted of questionnaire survey and direct physical examination. The questionnaire included genral characteristics of the subjects and oral health characteristics. The general characteristics consisted of subjective perception of health and chronic diseases. The oral health characteristics consisted of subjective oral health perception, dental caries, periodontal disease, annual oral examination, toothbrushing, prosthetics, implant surgery, and use of individual oral hygiene devices. Results: Those within 40 to 64 years old were the top users of oral hygiene devices. They perceived their dental hygiene was normal because they did not have periodontal disease but most of them had dental caries. They used oral hygiene devices three times a day and brushed teeth more than three times a day. They took annual dental checkup. Conclusions: It is necessary to promote the use of oral hygiene devices to prevent the dental caries and periodontal disease. The continuous training for the dental hygienists is very important because the dental hygienists is the first line of the prevention of dental caries and periodontal disease.